Grand Duke Alexis Visits Canada: Public Reception through a Diplomatic Lens - Farrow, Lee (Ontario History, 2014)
In 1871-1872, Grand Duke Alexis of Russia visited the United States and Canada over a period of three months, stopping in all the major cities of both countries and visiting sites like Niagara Falls. While in the United States, reception of the Duke was gushing and extravagant, his reception in Canada was much more subdued. While the extremely cold weather and the illness of the Prince of Wales explains some of this difference, it is also true that Canadians (and their British protectors) viewed the Russian-American friendship with trepidation and this influenced public reaction to the young Russian. British and Canadian newspapers followed the Grand Duke's progress through the United States, commenting in particular on American toadyism and hypocrisy in fawning over royalty, and suggesting that Canadians would take a different approach. Given the various calls for annexation from American politicians, and America's recent purchase of Alaska, it is understandable why Canadians and their British brethren might be concerned about the Russian-American friendship and underlying purpose of the Grand Duke's visit.